PENGGUNAAN MEDIA POHON PINTAR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI OPERASI HITUNG PEMBAGIAN SISWA KELAS IVA SD NEGERI GIRIAN INDAH - Tamboto, Fabyana Imelda; Titirloloby, Maria Petronela Riany (LPPM Institut Pendidikan Nusantara Global, 2023)
This research examines students' learning outcomes on Mathematics subjects of calculating operating material division in class IVA SD Country of Girian Indah. The problem in this study is that students' learning outcomes in Mathematics are still low. This research aims to improve the learning outcomes of Mathematics of Indah Girian Girian Country IVA Elementary students. The method in this study uses a class action research method. The subject of this study was 23 students in IVA. Data collection techniques are carried out through observations, interviews, tests, and documentation. Data analysis techniques use descriptive statistical analysis to illustrate about increasing the value of student learning outcomes. The results of this study indicate that the results of Mathematics learning increased, where in cycle I students were due to 17 students with a percentage of 74% and students who were not due to 6 students with a percentage of 26% with an average of 77. In cycle II student learning outcomes increase with a total number of students who have fallen by 22 students and students who are not due to 1 student, so that the percentage of student completion in cycle II reaches 96%.